2020
DOI: 10.1038/s41467-020-19245-3
|View full text |Cite
|
Sign up to set email alerts
|

Diastereodivergent chiral aldehyde catalysis for asymmetric 1,6-conjugated addition and Mannich reactions

Abstract: Chiral aldehyde catalysis is a burgeoning strategy for the catalytic asymmetric α-functionalization of aminomethyl compounds. However, the reaction types are limited and to date include no examples of stereodivergent catalysis. In this work, we disclose two chiral aldehyde-catalysed diastereodivergent reactions: a 1,6-conjugate addition of amino acids to para-quinone methides and a bio-inspired Mannich reaction of pyridinylmethanamines and imines. Both the syn- and anti-products of these two reactions can be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…The novel chiral 3-formyl BINOL aldehyde catalyst was displayed in the study of the Mannich reaction of 1,6-conjugated addition of amino acids (as shown in Figure 2) (Wen et al, 2020). The reaction went well in the presence of 4g chiral aldehyde and mesitylene as the solvent and tBuOK as a base, leading to good yields with 90% ee with enantioselectivity.…”
Section: Chiral Aldehyde Catalysis With Transition Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel chiral 3-formyl BINOL aldehyde catalyst was displayed in the study of the Mannich reaction of 1,6-conjugated addition of amino acids (as shown in Figure 2) (Wen et al, 2020). The reaction went well in the presence of 4g chiral aldehyde and mesitylene as the solvent and tBuOK as a base, leading to good yields with 90% ee with enantioselectivity.…”
Section: Chiral Aldehyde Catalysis With Transition Metalsmentioning
confidence: 99%
“…To demonstrate a stereoselective control, four potential reaction models were produced by DFT calculations. The key factor for the diastereoselectivity and enantioselectivity of catalysts is the steric FIGURE 2 | The 1,6-conjugated addition reaction by chiral BINOL aldehyde catalysts (Wen et al, 2020). effect of the R group.…”
Section: Chiral Aldehyde Catalysis With Transition Metalsmentioning
confidence: 99%
“…This approach is somewhat controversial due to the abovementioned utility of imidazolidine-2-ones as 1,2-diamines precursors. However, it is still used in some cases, especially with chiral diamines [ 4 , 5 , 6 , 7 ]. Novel approaches to these compounds have been developed in 2019–2020 by various research groups, indicating a growing area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, our group reported two diastereodivergent asymmetric transformations by chiral aldehyde catalysis. 5 Besides their use as organocatalysts, chiral aldehydes can also combine with other catalytic systems to achieve reactions that cannot be realized using single catalysis. In 2012, Aron et al reported a catalytic asymmetric α-allylation of methyl phenylalanine by a ternary catalytic system comprising picolinaldehyde, a Lewis acid, and a chiral ligand−palladium complex.…”
mentioning
confidence: 99%
“…In the same year, our group developed a BINOL-derived 2-formyl chiral-aldehyde-catalyzed nucleophilic addition of glycine derivatives, including glycine esters and glycine amides to enones, which led to optically active Δ(1)-pyrrolines in high yields . Recently, our group reported two diastereodivergent asymmetric transformations by chiral aldehyde catalysis . Besides their use as organocatalysts, chiral aldehydes can also combine with other catalytic systems to achieve reactions that cannot be realized using single catalysis.…”
mentioning
confidence: 99%